(untitled) (Studia Archaeologica, 2023)
Deer stone is a depiction of elegant artistic illustrations of deer and other animals and that was widespread throughout Mongolia and neighboring regions during the Late Bronze Age (13th-7th century BC). In recent years, as a result of extensive archaeological investigation in the northwestern region of Mongolia, a large number of new deer stones were discovered, which expands distribution and density of deer stones and provides new materials and insights into culture’s social understandings. In this article, we discussed 21 newly discovered deer stones that were found from the Uvs aimag in 2022. The Deer stone site Ivgeel contains the most number of deer stones in this region and the 4th deer stone stands in the center is taller than others and depicts numerous images, which might have been dedicated to the most high-status person. Moreover, it has revealed ochre paintings on carved images which are rarely encountered on deer stones. Увс аймгийн нутгаас шинээр илрүүлсэн буган хөшөөд Товчлол. Энэхүү өгүүлэлд 2022 оны хээрийн судалгааны явцад Увс аймгийн Малчин, Өмнөговь, Сагил, Тариалан, Ховд, Хяргас зэрэг сумдын нутгаас шинээр илрүүлсэн 21 тооны буган хөшөөний тархалт, дүрслэлийн онцлогийн талаар өгүүлжээ. Евроазийн тал нутагт хүрлийн хожуу үе буюу НТӨ XIII-VII зууны үед өргөн тархсан гайхамшигт нэгэн дурсгал бол буган хөшөө бөгөөд дайчин баатар эрийг төлөөлүүлэн дүрсэлсэн чулуун хөшөө мөн болохыг ихэнх судлаачид дэмжсэн байдаг. Монголын баруун хойд бүс нутагт сүүлийн жилүүдэд археологийн судалгаа өргөн хүрээтэй хийгдсэний үр дүнд шинээр олон тооны буган хөшөөд илэрч олдож буй бөгөөд бид өмнөх судалгааны хэрэглэгдэхүүнийг шинэ материалаар нэмж баяжуулах, зарим онцлог дүрслэлийг дэлгэрэнгүй тайлбарлахыг зорьсон болно. Түлхүүр үг: Буган хөшөө, хүрлийн хожуу үе, зосон будаг, зэр зэвсэг